2017
DOI: 10.1542/peds.2017-2295
|View full text |Cite
|
Sign up to set email alerts
|

Momentary Parental Stress and Food-Related Parenting Practices

Abstract: Clinicians may want to consider discussing with parents the influence stress and depressed mood can have on everyday food-related parenting practices. Additionally, future researchers should consider using real-time interventions to reduce parental stress and depressed mood to promote healthy parent food-related parenting practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 37 publications
6
84
0
3
Order By: Relevance
“…Findings from this study align with, the work of Berge and colleagues which explored the momentary impact of parental stress and mood, measured using ecological momentary assessment (EMA), on use of coercive food parenting practices; parental stress was found to be associated with an increase in the use of coercive food parenting practices the same evening. 34,35 Further, previous research supports the idea that parents often report engaging in multiple, sometimes even counterintuitive, feeding strategies; for example, previous work by the lead author found that many parents of adolescents reported high levels of both food restriction and pressure-to-eat. 18 At the time, it was posited that parents might use different strategies for different foods and the current research broadens this potential explanation by suggesting that parents may be using multiple practices across all three domains within the context of one eating occasion.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Findings from this study align with, the work of Berge and colleagues which explored the momentary impact of parental stress and mood, measured using ecological momentary assessment (EMA), on use of coercive food parenting practices; parental stress was found to be associated with an increase in the use of coercive food parenting practices the same evening. 34,35 Further, previous research supports the idea that parents often report engaging in multiple, sometimes even counterintuitive, feeding strategies; for example, previous work by the lead author found that many parents of adolescents reported high levels of both food restriction and pressure-to-eat. 18 At the time, it was posited that parents might use different strategies for different foods and the current research broadens this potential explanation by suggesting that parents may be using multiple practices across all three domains within the context of one eating occasion.…”
Section: Discussionmentioning
confidence: 78%
“…other children, job requirements); it is easy to imagine how a parent might shift their approach to feeding day-to-day or moment-to-moment, based on changes to these momentary factors. In fact, two recent publications by Berge and colleagues utilizing ecological momentary assessment (EMA) methods, found that momentary parental stress and mood, played a salient role in the use of coercive food-related parenting practices; 34,35 higher parental stress and greater depressed mood earlier in the day were found to predict greater use of pressure-to-eat feeding behaviors later the same evening. Long term, developing an understanding of momentary factors that influence a parent’s use of particular food-related parenting practices across multiple contexts will facilitate the development of improved measures of the use and impact of food-related parenting practices, as well as effective interventions aimed at promoting the use of appropriate food-related parenting practices.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the high level of experience and long-standing training in stress management in long-career employees. On the other hand, emergency services personnel may be used to address stressful situations, as they are part of a coordinated and ordered emergency response and have to constantly handle very high levels of stress [27,28].…”
Section: Need For Psychological Supportmentioning
confidence: 99%
“…Though participants were not asked specifically about their level of stress we can infer that both child and parent problem behaviors such as the ones identified as problematic place a strain on the family. Restrictive, self-limiting, and/or negative child feeding behaviors are also observed in infants, toddlers, and children with cystic fibrosis (Berge et al, 2017;Chatoor, 2009;Driscoll et al, 2015;Mehta et al, 2018;Rogers, Ramsay, & Blissett, 2018). In a study by Driscoll and colleagues (Driscoll et al, 2015), children with cystic fibrosis demonstrated a higher frequency of textured food refusal, general food refusal, stalling, and picky eating compared to normal, healthy feeding peers.…”
Section: Discussionmentioning
confidence: 99%
“…Parents stressed about their child's nutritional intake have been shown to be more likely to use pressure-to-eat feeding practices (Berge et al, 2017) and to use less encouraging language when describing their child's diet (Rogers et al, 2018). Use of negative mealtime strategies by parents has been associated with children demonstrating more self-limiting behaviors during oral intake.…”
Section: Discussionmentioning
confidence: 99%